Impacts of ENSO on air‐sea oxygen exchange: Observations and mechanisms. Issue 5 (30th May 2017) - Eddebbar, Yassir A.; Long, Matthew C.; Resplandy, Laure; Rödenbeck, Christian; Rodgers, Keith B.; Manizza, Manfredi; Keeling, Ralph F.
Abstract: Models and observations of atmospheric potential oxygen (APO ≃ O2  + 1.1 * CO2 ) are used to investigate the influence of El Niño–Southern Oscillation (ENSO) on air‐sea O2 exchange. An atmospheric transport inversion of APO data from the Scripps flask network shows significant interannual variability in tropical APO fluxes that is positively correlated with the Niño3.4 index, indicating anomalous ocean outgassing of APO during El Niño. Hindcast simulations of the Community Earth System Model (CESM) and the Institut Pierre‐Simon Laplace model show similar APO sensitivity to ENSO, differing from the Geophysical Fluid Dynamics Laboratory model, which shows an opposite APO response. In all models, O2 accounts for most APO flux variations. Detailed analysis in CESM shows that the O2 response is driven primarily by ENSO modulation of the source and rate of equatorial upwelling, which moderates the intensity of O2 uptake due to vertical transport of low‐O2 waters. These upwelling changes dominate over counteracting effects of biological productivity and thermally driven O2 exchange. During El Niño, shallower and weaker upwelling leads to anomalous O2 outgassing, whereas deeper and intensified upwelling during La Niña drives enhanced O2 uptake. This response is strongly localized along the central and eastern equatorial Pacific, leading to an equatorial zonal dipole in atmospheric anomalies of APO. This dipole is further intensified by ENSO‐related changes in winds, reconciling apparently conflicting APO observations in the tropical Pacific. These findings suggest a substantial and complex response of the oceanic O2 cycle to climate variability that is significantly (>50%) underestimated in magnitude by ocean models. Key Points: ENSO drives significant variability in tropical Pacific air‐sea O2 exchange The O2 flux response to ENSO is driven primarily by ocean dynamics Atmospheric transport acts to amplify ENSO‐related anomalies in atmospheric O2